Critical Thinking Analysis of Junior High School Students on Temperature Topic during Virtual Learning - Solehudin, Aji; Riandi, Riandi; Hidayat, Arif; Hendayana, Sumar (FKIP Universitas Lampung, 2021)
This article aims to analyze students' critical thinking skills of temperature topic through virtual learning at junior high schools. The method used in this research was descriptive qualitative with a case study approach. This research was conducted at seventh grade of the junior high school in Bandung, West Java. The instruments used is observation. The collected data were analyzed using Transcript Based Lesson Analysis (TBLA) to analyze student’s dialogue. The results indicated that two out of the twelve indicators of critical thinking skills during virtual learning were developed. The two indicators are focusing on questions and the second is asking and answering questions. The low achievement of students' critical thinking skills is due to the limited time on virtual learning. Which is limited, so that teachers often apply learning method through transferring knowledge. Analysis of student activities and dialogue during virtual learning can be a source of teacher’s reflection for making further improvement.Keywords: critical thinking skill, temperature topic, virtual learning. DOI: http://dx.doi.org/10.23960/jpmipa/v22i2.pp305-314